Nawa Dewata Hinduistik dan Walisongo: Role-Model Dakwah Walisongo - Lufaefi Lufaefi; Zahro Nur Amalia (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
Islam is a religion of compassion. This fact is different from the majority of followers who translate it in all segments of life in a formalistic form, so that the compassionate identity of Islam is often mortgaged. Islam is exclusive with other religions and beliefs. As a result, Islam is also difficult to expand and accused of being a rigid and exclusive religion. Islam that was born and developed in the archipelago practiced by Walisongo is flexible with other beliefs. One of its practices Walisongo succeeded in taking inspiration from the Hinduism of the Hindu Nawa Dewata to become Sufistic trustees. The nine deities in Hinduism were replaced by nine saints who later became known as Walisongo. Through Walisongo's da'wah analysis Islamizing other religions, namely theological approach, games and cultural accuracy, it was found that the change in cosmology of Nawa Dewata became Walisongo because in Islam and Hinduism both contained values of compassion, compassion, and intertwining among creatures God. The saints carried out the takeover by prioritizing three main principles, namely prioritizing the interests of the community over him, compassion as the concept of a human unity with God, and an emotional approach. All three make Islam easily understood as a religion of affection, so that it is easily accepted by Hindus.